Answer:
![f(x)=\mleft\{\begin{aligned}-0.5x+3,if-6\le x\le-2 \\ -3,if-2<strong>Explanation:</strong><p>For the value of x such that: -6≤x≤-2</p><p>We have the endpoints (-6,0) and (-2, -2).</p><p>We determine the equation in the slope-intercept form, y=mx+b.</p>[tex]\begin{gathered} \text{Slope,m}=(0-(-2))/(-6-(-2)) \\ =(2)/(-6+2) \\ =(2)/(-4) \\ m=-0.5 \end{gathered}]()
The equation then becomes:

Using the point (-6,0)

Therefore: f(x)=-0.5x+3, -6≤x≤-2
Next, f(x)=-3 for -2
Finally, for 1The endpoints are (1,-4) and (6,1)

Using the point (1,-4)

Therefore, f(x)=x-5, for 1
The completed function will now be:
[tex]f(x)=\mleft\{\begin{aligned}-0.5x+3,-6\le x\le-2 \\ -3,-2